Building Little Italy: Philadelphia's ltalians before Mass Migration - Zucchi, John (Labour / Le Travail, 2000)
The article reviews the book, "Building Little Italy: Philadelphia's Italians before Mass Migration," by Richard N. Juliani.

Solidarity or Survival: Americon Labor and European Immigrants, 1830-1924 - Zucchi, John E. (Labour / Le Travail, 1989)
The article reviews the book, "Solidarity or Survival: American Labor and European Immigrants, 1830-1924," by A. T. Lane.
Keywords: LANE; A. T.; Labor Unions; Nonfiction; REVIEWS; SOLIDARITY or Survival: American Labor & European Immigrants 1830-1924 (Book); books

DP: Lithuanian Immigration to Canada after the Second World War - Zucchi, John E. (Labour / Le Travail, 1988)
The article reviews the book, "DP: Lithuanian Immigration to Canada after the Second World War," by Milda Danys.

An Italian Passage: Immigrants to Three American Cities, 1890-1930 - Zucchi, John E. (Labour / Le Travail, 1981)
This article reviews the book, "An Italian Passage: Immigrants to Three American Cities, 1890-1930," by John W. Briggs.